First Methodist Church centennial celebration - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a performance during the First Methodist Church centennial celebration. On stage a man stands at a microphone and several people are seated house right. A man sits at a piano house left. The set is decorated with a large number 100. The audience appears to be seated at several tables.